DEVELOPMENT OF CLUSTER PARTNERSHIP SYSTEMS AS AN OBJECT OF STATE REGULATION - Shkoda, Mariana S. (Journal of Strategic Economic Research, 2023)
The article provides a thorough analysis of evolutionary research on the development of cluster formations and their global connections as an object of state administration. In the course of the study, the growing interconnection of cluster partnership systems is reflected, where resources and competences are combined, access to target markets and know-how becomes open, information and experience are exchanged between clusters, network systems are created using special technology, it becomes possible to use sources of knowledge with of the whole world and the development of a new field of knowledge. The existing approaches of scientists in terms of interregional and intercluster partnership are emphasized, it is highlighted that a significant number of authors describe systems of interaction in partnership, but do not explain the purpose of this process. However, eliminating the fact that researchers do not have a single opinion about the quintessence of cluster partnership systems both at the level of regions, industries, and clusters, it is justified that the researched ideas of scientists can be used in the development of the author's interpretation of the category of "cluster partnership systems". It is emphasized that all the considered approaches are complementary to the studied category. Each approach brings its own understanding of this concept. Accordingly, the author emphasized that the consideration of cluster partnership systems from the standpoint of only one approach does not give a complete idea of their essence and, when developing state programs for the development of cluster partnership systems, it is necessary to use these scientific concepts in various combinations, which will allow to objectively evaluate the activities of all economic partnership entities that provide innovative development of the national economy and will create a synergistic effect of the interaction of participants from the standpoint of strategic and transactional approaches.